Knowledge and Practices of Post Cesarean Section Mothers Towards Self-Care After Delivery at Mbarara Regional Referral Hospital. - Solomon Atuhaire (Student's Journal of Health Research, 2021)
ABSTRACT Background: It is recommended to all mothers to undergo post-cesarean section self-care after delivery up to six weeks. However, many mothers return to Mbarara Regional Referral Hospital as a result of getting some complications related to cesarean section. The reasons why these mothers develop these complications are not clear and possible other practices performed by delivered mothers to solve their post-delivery challenges are not yet documented. Methods: The design of this study was a descriptive cross-sectional study design and a semi-structured questionnaire was used to collect quantitative data from the participants. Data were collected from 150 mothers admitted to the Maternity ward of Mbarara Regional Referral Hospital who formed the inclusion criteria and accepted to participate in the study. Data was captured using Microsoft excel and analyzed using Statistical Package for social sciences (SPSS). Results: The response rate in this study was 100%. The knowledge of post-cesarean section self-care among postpartum women at MRRH in Mbarara was poor as the majority of the participants 90(60%) reported to have never heard about Post Cesarean self-care while only 60 (40%) reported having ever heard about Post Cesarean self-care and no postpartum woman was fully aware of all the aspects of PCS and only 26% could talk of more than 2 aspects of the PCS. The findings of the study also revealed that 22% (33) of the postpartum women don't perform PCS at all. This shows a low practice of PCS among postpartum women. Conclusion and recommendations: Generally, in this study, the knowledge of post-cesarean section self-care among postpartum women at MRRH in Mbarara was poor, suggesting that these postpartum women are unaware of the value of this personal health promotion tool.